A high-efficiency enhanced shotcrete admixture and its application
Through the combination of polycarboxylic acid water reducer, plant glue and nanofiber and epoxy resin composite, the problem of high rebound rate of sprayed concrete is solved, the early strength and quality of use are improved, and more efficient water resource utilization is achieved. Reduce pollution.
Patent Information
- Application Number
- CN202310563384.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-18
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2043-05-18
Smart Images

Figure BDA0004235846120000051 
Figure BDA0004235846120000052 
Figure BDA0004235846120000061
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of concrete admixtures, and more specifically, to a high-efficiency reinforced shotcrete admixture and application thereof. Background Art
[0002] Shotcrete refers to concrete that is sprayed and poured with a pressure spray gun. It has the advantages of fast setting and hardening, high early strength, and saving support formwork. It is widely used in projects such as initial support and structural reinforcement of tunnel linings, walls, mines, and underground comprehensive pipelines.
[0003] At present, shotcrete still has poor fluidity and collapse protection effect, and there is a phenomenon of random "adding water" during on-site shotcrete construction. After adding water to shotcrete, the amount of free water increases, and more accelerating components are needed for coagulation and hardening. Therefore, the free water consumption capacity is reduced, the coagulation and hardening time is prolonged, and the rebound rate of the shotcrete increases, causing greater pollution and waste, while affecting the early performance and quality of concrete. Therefore, it is very necessary to develop an admixture that can reduce the rebound rate of shotcrete.
[0004] In the related art, the rebound rate is reduced by adding admixtures and organic surfactants to the shotcrete to accelerate the setting, but the effect of reducing the rebound rate is general and it will also affect the later strength of the concrete, which is difficult to meet the actual use requirements. Summary of the invention
[0005] In order to reduce the rebound rate of shotcrete admixtures, the present application provides a high-efficiency enhanced shotcrete admixture and a preparation method thereof.
[0006] In the first aspect, the present application provides a highly efficient reinforced shotcrete admixture, which adopts the following technical solution:
[0007] A high-efficiency enhanced shotcrete admixture, comprising the following raw materials in parts by weight: 10-30 parts of polycarboxylate water reducer; 15-30 parts of plant glue; 80-110 parts of nanofiber and epoxy resin composite; 30-70 parts of accelerating setting agent; 5-10 parts of water;
[0008] The nanofiber and epoxy resin composite is a composite of long-chain silane-modified nanofiber and fluorine-containing epoxy resin emulsion.
[0009] The high-efficiency enhanced shotcrete admixture of the present application can be selected from 10-30 parts of polycarboxylic acid water reducer; 15-30 parts of vegetable glue; 80-110 parts of nanofiber and epoxy resin composite; 30-70 parts of accelerator; 5-10 parts of water; and any value within the respective ranges can be selected for the admixture raw materials.
[0010] Through the above technical scheme, the addition of polycarboxylate water reducer plays a role in dispersing the concrete raw materials, improving the working performance, reducing the unit water consumption, effectively fixing the free water, and improving the cohesiveness of the slurry to increase the wrapping between the slurry and the aggregate, improve the fluidity of the shotcrete, improve the cohesiveness, and play a role in reducing the rebound rate of the shotcrete; the addition of plant gum, the plant gum adsorbs the polymer molecules in the shotcrete on the surface of the cement particles, connects the cement particles with each other to form a flocculation agglomeration structure, the flocculation agglomeration structure wraps part of the free water inside the structure, disperses the moisture between the particles of the shotcrete raw materials, and can also promote the formation of a bridge chain structure or a network structure between the long-chain organic matter and the inorganic particles in the shotcrete, thereby increasing the effect between the cement particles to improve the cohesiveness of the slurry; reduce the fluidity of the shotcrete, and reduce the rebound rate of the shotcrete; the addition of the accelerator can accelerate the speed at which the concrete changes from a slurry to a solid state, shorten the hardening time of the shotcrete, meet the requirements of reducing the rebound rate of the shotcrete, and improve the early strength of the shotcrete; the addition of water promotes the mixing of the shotcrete raw materials.
[0011] The composite of nanofiber and epoxy resin can improve the cohesion of shotcrete admixtures and reduce the rebound rate of shotcrete.
[0012] In the composite of long-chain silane-modified nanofibers and fluorine-containing epoxy resin emulsion, silane can form chemical bonds with nanofibers, and Si-O bonds can also be introduced into the epoxy system to form an interpenetrating cross-linked network. The composite of nanofibers and epoxy resin can increase the cross-linking density of the entire system and improve the adhesion between the raw materials of shotcrete. At the same time, the long chain of silane can reduce the surface energy of the composite, and the fluorine atoms in the fluorine-containing epoxy resin have strong electronegativity. Both can give the composite surface hydrophobic properties, which can not only improve the fluidity of shotcrete, but also improve the cohesion of shotcrete, thereby reducing the rebound rate of shotcrete.
[0013] Preferably, the nanofiber and epoxy resin composite is a composite of long-chain silane-modified nanofiber and fluorine-containing epoxy resin emulsion prepared by the following steps:
[0014] Step S1: 2-8 kg of toluene diisocyanate is dissolved in an organic solvent, heated to 50-100° C., stirred, a catalyst is added, reacted for 1-3 hours, 2-8 kg of fluorine-containing organic matter is added, washed and dried to obtain a fluorine-containing modifier;
[0015] Step S2: after mixing the fluorine-containing modifier prepared in step S1, 10-20 kg of bisphenol A diglycidyl ether, and 3-5 kg of diluent, 0.3-1 kg of curing agent is added, and curing is performed at 80-150° C. for 5-8 hours to obtain a fluorine-containing epoxy resin emulsion;
[0016] Step S3: Under acidic conditions, add 2-10 kg of long-chain silane to ethanol and water solution, heat and stir, then add 50-80 kg of nanofibers and stir, after drying, add fluorinated epoxy resin obtained in step S2 and 8-16 kg of co-solvent, heat and stir, then wash and dry to obtain a long-chain silane-modified nanofiber and fluorinated epoxy resin emulsion composite.
[0017] According to the technical scheme, first, toluene diisocyanate is added as an accelerator, and a fluorine-containing modifier is prepared under the action of the toluene diisocyanate accelerator and a catalyst; then, a fluorine-containing epoxy resin emulsion is prepared under the action of the fluorine-containing modifier, bisphenol A diglycidyl ether, a diluent and a curing agent; under acidic conditions, long-chain silane depolymerized in ethanol and aqueous solution and nanofibers and fluorine-containing epoxy resin emulsion are prepared under the action of a cosolvent to obtain a long-chain silane-modified nanofiber and fluorine-containing epoxy resin emulsion composite, the long-chain silane depolymerized under acidic conditions and the nanofibers are cross-linked through chemical bonds, and can also react with the epoxy resin to form an interpenetrating network, and the cross-linking density of the composite is improved under the promotion of the cosolvent, thereby improving the cohesiveness of the shotcrete and reducing the rebound rate of the shotcrete.
[0018] Preferably, the co-solvent is a mixture of lauric acid and ethylene glycol butyl ether.
[0019] Through the above technical scheme, lauric acid can activate the silanol groups of silane and hydrolyze the hydroxyl groups on the surface of the fiber, thereby increasing the solubility of the chain silane-modified nanofibers in the fluorinated epoxy resin. Ethylene glycol butyl ether can improve the compatibility of the long-chain silane-modified nanofibers and the fluorinated epoxy resin emulsion composite. The combined use of the two can improve the crosslinking density of the long-chain silane-modified nanofibers and the fluorinated epoxy resin emulsion composite, increase the cohesiveness of the composite, and reduce the rebound rate of the shotcrete.
[0020] Preferably, the weight ratio of lauric acid to ethylene glycol butyl ether is 1:(1-2).
[0021] Through the above technical scheme, the weight ratio of lauric acid and ethylene glycol butyl ether is controlled to be 1: (1-2), thereby further improving the compatibility of the long-chain silane-modified nanofibers and the fluorine-containing epoxy resin emulsion composite, thereby reducing the rebound rate of the shotcrete.
[0022] Preferably, the vegetable gum is selected from at least one of wenan gum, xanthan gum and konjac gum.
[0023] Through the above technical scheme, Wenlun gum, xanthan gum and konjac gum have good thickening properties, acid and alkali resistance, water retention and high temperature resistance, can improve the viscosity of shotcrete, reduce its fluidity, and thus reduce the rebound rate of shotcrete.
[0024] Preferably, the raw materials further include 5-20 parts by weight of sulfonic acid modified polyacrylic acid emulsion.
[0025] Through the above technical scheme, the sulfonic acid modified polyacrylic acid emulsion will provide a bridging effect to bridge the raw material particles in the shotcrete to increase the slurry yield stress and plastic cohesion, intramolecular crosslinking and intermolecular crosslinking, increase the cohesion of the concrete, and form hydrogen bonds with water to limit the movement of free water, improve its fluidity, and thereby reduce the rebound rate of the shotcrete.
[0026] Preferably, the sulfonic acid modified polyacrylic acid emulsion is prepared by the following steps:
[0027] Acrylic acid monomer, sodium allyl sulfonate, methylene bisacrylamide and vinyl acetate are mixed, heated to 30-50°C, then a chain transfer agent and an initiator are added and stirred for reaction, and finally hydrogen peroxide is added and stirred for 10 minutes to obtain a sulfonic acid modified polyacrylic acid emulsion.
[0028] Through the above technical scheme, acrylic acid monomer, sodium allyl sulfonate, methylene bisacrylamide and vinyl acetate are heated to 30-50°C, and under the action of chain transfer agent and redox system initiator, sulfonic acid modified polyacrylic acid emulsion is prepared, which can bridge cement particles together to increase the plastic viscosity of the slurry, and the polymer in the emulsion will form intramolecular crosslinking and intermolecular crosslinking to increase the liquid phase viscosity. At the same time, the sulfonic acid modified polyacrylic acid emulsion will also form hydrogen bonds with water to reduce the amount of free water, which is helpful to increase the plastic viscosity of the slurry and thus reduce the rebound rate of the shotcrete.
[0029] Preferably, the weight ratio of methylenebisacrylamide to vinyl acetate is 1:(1.2-2).
[0030] Through the above technical scheme, in the preparation of sulfonic acid modified polyacrylic acid emulsion, the weight ratio of methylenebisacrylamide and vinyl acetate is controlled, which can enhance the cross-linking effect of polyacrylic acid emulsion and is beneficial to the stability of polyacrylic acid emulsion. The dual effect of the two can not only increase the plastic viscosity of sulfonic acid modified polyacrylic acid emulsion, reduce its fluidity, but also further reduce the rebound rate of shotcrete.
[0031] Preferably, the weight ratio of the sulfonic acid modified polyacrylic acid emulsion to the polycarboxylic acid water reducer is (0.5-0.8):1.
[0032] Through the above technical scheme, by controlling the ratio of polycarboxylic acid water-reducing agent and sulfonic acid modified polyacrylic acid emulsion, the early-strength water-reducing agent and sulfonic acid modified polyacrylic acid emulsion with certain early strength performance enhance the adsorption-dispersion performance of the polycarboxylic acid water-reducing agent, and weaken the delay of the polycarboxylic acid water-reducing agent on cement hydration, so that the concrete solidifies quickly at an early stage, and further reduce the rebound rate of the shotcrete.
[0033] In a second aspect, the present application provides the use of any of the above-mentioned high-efficiency enhanced shotcrete admixtures in shotcrete, wherein the addition amount of the high-efficiency enhanced shotcrete admixture is 0.5-8% of the mass of cement.
[0034] In summary, the present application includes at least one of the following beneficial technical effects:
[0035] (1) In the present application, by adjusting the types and dosages of various raw materials, and the nanofiber and epoxy resin composite in the raw materials is a composite of long-chain silane-modified nanofiber and fluorine-containing epoxy resin emulsion, the rebound rate of the high-efficiency enhanced shotcrete obtained is as low as 6.25%, thereby effectively reducing the rebound rate of the high-efficiency enhanced shotcrete.
[0036] (2) In the present application, sulfonic acid-modified polyacrylic acid emulsion is added to the raw materials of the high-efficiency enhanced shotcrete admixture, so that the rebound rate of the high-efficiency enhanced shotcrete is 8.95%, which further reduces the rebound rate of the high-efficiency enhanced shotcrete.
[0037] (3) The present application adds sulfonic acid modified polyacrylic acid emulsion to the raw materials of high-efficiency enhanced shotcrete admixture and controls the weight ratio of methylene bisacrylamide and vinyl acetate to obtain a rebound rate of high-efficiency enhanced shotcrete of 8.36%, further reducing the rebound rate of high-efficiency enhanced shotcrete.
[0038] (4) The present application adds a co-solvent which is a mixture of lauric acid and ethylene glycol butyl ether to the raw materials in the composite of long-chain silane-modified nanofibers and fluorinated epoxy resin emulsion, and controls the weight ratio of lauric acid and ethylene glycol butyl ether to obtain a rebound rate of 6.95% for high-efficiency enhanced shotcrete, thereby further reducing the rebound rate of high-efficiency enhanced shotcrete.
[0039] (5) The present application controls the weight ratio of methylenebisacrylamide and vinyl acetate in the raw materials for preparing the sulfonic acid modified polyacrylic acid emulsion, and the rebound rate of the obtained high-efficiency enhanced shotcrete is 6.25%, which further reduces the rebound rate of the high-efficiency enhanced shotcrete. DETAILED DESCRIPTION
[0040] The present application is further described in detail below in conjunction with specific embodiments.
[0041] The following raw materials in this application are all commercially available products, which are intended to fully disclose the raw materials in this application and should not be construed as limiting the sources of the raw materials. Specifically:
[0042] The catalyst is dibutyltin dilaurate, with a content of 98%; the fluorine-containing organic compound is 3-fluorocatechol, with a content of 98%; the long-chain silane is hexadecyldimethylchlorosilane, with a content of 98%; the diluent is epichlorohydrin, with a content of 98%; the curing agent is hexamethylenediamine, with a content of 99%; the chain transfer agent is thioglycolic acid, with a content of 98%; the initiator is sodium dodecyl sulfate (SDS) and hexadecanol redox system, SDS, with a content of 98%, hexadecanol, with a content of 98%; propylene trimethoxysilane, with a content of 95%; and catechol, with a content of 98%.
[0043] The following is an example of the preparation of nanofiber and epoxy resin composites
[0044] Preparation Example 1
[0045] The nanofiber and epoxy resin composite of Preparation Example 1 is prepared by the following steps:
[0046] Step S1: 4 kg of toluene diisocyanate was dissolved in an organic solvent, heated to 75° C., stirred for 30 min, 0.1 kg of dibutyltin dilaurate (catalyst) was added, reacted for 2 h, 2 kg of 3-fluorocatechol (fluorine-containing organic matter) was added, washed, and vacuum dried for 3 h to obtain a fluorine-containing modifier;
[0047] Step S2: after mixing the fluorine-containing modifier prepared in step S1, 15kg of bisphenol A diglycidyl ether, and 4kg of (epichlorohydrin) diluent, add 0.65kg of hexamethylenediamine (curing agent), and cure at 120°C for 7h to obtain a fluorine-containing epoxy resin emulsion; Step S3: add 0.5kg of glacial acetic acid to the ethanol and aqueous solution, stir evenly, 6kg of hexadecyldimethylsilyl chloride (long-chain silane), heat to 55°C and stir for 1h, then add 65kg of nanofibers and stir, after drying, add the fluorine-containing epoxy resin obtained in step S2 and 8kg of lauric acid (cosolvent), heat to 70°C and stir for 30min, then wash and vacuum dry to obtain a composite of long-chain silane-modified nanofibers and fluorine-containing epoxy resin emulsion.
[0048] Preparation Example 2-3
[0049] The operation steps of preparing the nanofiber and epoxy resin composite of Example 2-3 are the same as those of Example 1, except that the amount of the fluorine-containing organic compound, ie, 3-fluorocatechol, is different, as shown in Table 1 for details.
[0050] Table 1 Raw materials of the composite of nanofiber and epoxy resin in preparation example 2-3 (kg)
[0051]
[0052] Preparation Example 4-10
[0053] The operation steps of preparing the nanofiber and epoxy resin composite of Examples 4-10 are the same as those of Preparation Example 3, except that the type and amount of the co-solvent are different, as shown in Table 2 for details.
[0054] Table 2 Raw materials of the composite of nanofiber and epoxy resin in preparation examples 4-10 (kg)
[0055]
[0056]
[0057] The following is an example of the preparation of sulfonic acid modified polyacrylic acid emulsion:
[0058] Preparation Example 11
[0059] The sulfonic acid modified polyacrylic acid emulsion of Preparation Example 11 was prepared by the following steps:
[0060] 3 kg of acrylic acid monomer, 2.1 kg of sodium allyl sulfonate, 0.8 kg of methylene bisacrylamide and 0.8 kg of vinyl acetate were mixed and stirred evenly, heated to 40° C., and then 1.2 kg of thioglycolic acid (chain transfer agent), 0.8 kg of sodium dodecyl sulfate (SDS) and 0.62 kg of hexadecanol (initiator) were added and stirred for 40 minutes to obtain a sulfonic acid modified polyacrylic acid emulsion.
[0061] Preparation Examples 12-15
[0062] The operation steps of preparing the sulfonic acid modified polyacrylic acid emulsions of Examples 12-15 are the same as those of Example 10, except that the amount of vinyl acetate used is different, as shown in Table 3 for details.
[0063] Table 3 Raw materials of sulfonic acid modified polyacrylic acid emulsion of preparation examples 12-15 (kg)
[0064]
[0065] The following is an embodiment of a highly efficient enhanced shotcrete admixture
[0066] Example 1
[0067] The high-efficiency enhanced shotcrete admixture of Example 1 includes the following raw materials: 20 kg of polycarboxylate water reducer; 18 kg of Wenlun glue (plant glue); 50 kg of accelerator; 8 kg of water; wherein 80 kg of the nanofiber and epoxy resin composite is the nanofiber and epoxy resin composite prepared in Preparation Example 1. The high-efficiency enhanced shotcrete admixture is prepared by the following steps: weighing the raw materials according to the raw material composition, mixing them, and stirring them evenly to obtain the high-efficiency enhanced shotcrete admixture.
[0068] Example 2-3
[0069] The raw materials of the high-efficiency enhanced shotcrete admixture of Example 2-3 are the same as those of Example 1, except that the dosage of the nanofiber and epoxy resin composite in the raw materials is different, as shown in Table 4 for details.
[0070] Table 4 Example 2-3 High-efficiency enhanced shotcrete admixture (kg)
[0071]
[0072] Example 4
[0073] The raw materials of the high-efficiency enhanced shotcrete admixture of Example 4 are the same as those of Example 3, except that the sulfonic acid-modified polyacrylic acid emulsion prepared in Preparation Example 11 is added to the raw materials.
[0074] Embodiment 5-8
[0075] The raw materials of the high-efficiency enhanced shotcrete admixtures of Examples 5-8 are the same as those of Example 4, except that the amounts of the polycarboxylic acid water-reducing agent and the sulfonic acid-modified polyacrylic acid emulsion in the raw materials are different, as shown in Table 5 for details.
[0076] Table 5 Example 5-8 High-efficiency enhanced shotcrete admixture (kg)
[0077]
[0078] Examples 9-17
[0079] The raw materials of the high-efficiency enhanced shotcrete admixtures of Examples 9-17 are the same as those of Example 6, except that the nanofiber and epoxy resin composite in the raw materials is the nanofiber and epoxy resin composite prepared in Preparation Examples 2-10.
[0080] Examples 18-21
[0081] The raw materials of the high-efficiency enhanced shotcrete admixtures of Examples 18-21 are the same as those of Example 6, except that the sulfonic acid-modified polyacrylic acid emulsion in the raw materials is the sulfonic acid-modified polyacrylic acid emulsion prepared in Preparation Examples 12-15.
[0082] Comparative Example 1
[0083] The raw materials of the high-efficiency enhanced shotcrete admixture of Comparative Example 1 are the same as those of Example 1, except that the nanofiber and epoxy resin composite in the raw materials are replaced by unmodified nanofiber and epoxy resin composite in equal amounts, and the other raw material types and dosages are the same as those of Example 1; specifically, in the preparation of the nanofiber and epoxy resin composite, 2kg of 3-fluorocatechol (fluorinated organic matter) in step S1 is replaced by 2kg of catechol, and 6kg of hexadecyldimethylchlorosilane (long-chain silane) in step S3 is replaced by 6kg of propylene trimethoxysilane.
[0084] Comparative Example 2
[0085] The raw materials of the high-efficiency enhanced shotcrete admixture of Comparative Example 2 are the same as those of Example 1, except that the nanofiber and epoxy resin composite in the raw materials are replaced by an equal amount of a nanofiber and epoxy resin emulsion composite only modified by long-chain silane, and the other raw material types and dosages are the same as those of Example 1; specifically, in the preparation of the nanofiber and epoxy resin composite, 2 kg of 3-fluorocatechol (fluorinated organic matter) in step S1 is replaced by 2 kg of catechol.
[0086] Comparative Example 3
[0087] The raw materials of the high-efficiency enhanced shotcrete admixture of Comparative Example 3 are the same as those of Example 1, except that the nanofiber and epoxy resin composite in the raw materials is replaced by an equal amount of nanofiber and fluorine-containing epoxy resin emulsion composite, and the other raw material types and dosages are the same as those of Example 1; specifically, in the preparation of the nanofiber and epoxy resin composite, 6 kg of hexadecyldimethylchlorosilane (long-chain silane) in step S3 is replaced by 6 kg of propylene trimethoxysilane.
[0088] Comparative Example 4
[0089] The raw materials of the high-efficiency enhanced shotcrete admixture of Comparative Example 4 are the same as those of Example 1, except that the nanofibers and epoxy resin composites in the raw materials are replaced by long-chain silane-modified nanofibers in equal amounts, and the types and dosages of other raw materials are the same as those of Example 1; specifically, in the preparation of the nanofiber and epoxy resin composite, only step S3 is included, and no epoxy resin is added.
[0090] Comparative Example 5
[0091] The raw materials of the high-efficiency enhanced shotcrete admixture of Comparative Example 5 are the same as those of Example 1, except that the nanofiber and epoxy resin composite in the raw materials replace the fluorine-containing epoxy resin emulsion in equal amounts, and the other raw material types and dosages are the same as those of Example 1; specifically, in the preparation of the nanofiber and epoxy resin composite, only the preparation process of step S1 and step S2 is included.
[0092] The following are examples of applications of high-efficiency enhanced shotcrete
[0093] Application Example 1
[0094] The raw materials of the high-efficiency enhanced shotcrete of Application Example 1 include: 450kg cement, 200kg fly ash, 900kg sand, 175kg water, and 23kg high-efficiency enhanced shotcrete admixture.
[0095] Application Example 2-21
[0096] The raw materials of the high-efficiency reinforced shotcrete of Application Example 2-21 are the same as those of Application Example 1, except that the high-efficiency reinforced shotcrete admixture is the high-efficiency reinforced shotcrete admixture of Example 2-21.
[0097] Application Comparative Examples 1-5
[0098] The raw materials of the high-efficiency reinforced shotcrete of Application Examples 1-5 are the same as those of Application Example 1, except that the high-efficiency reinforced shotcrete admixture is the high-efficiency reinforced shotcrete admixture of Comparative Examples 1-5.
[0099] Performance Testing
[0100] The following testing standards or methods were used to perform performance tests on the high-efficiency reinforced shotcrete obtained from different application examples 1-21 and application comparison examples 1-5. The test results are shown in Table 6.
[0101] Impact strength, 7d compressive strength and 28d compressive strength: The impact strength, 7d compressive strength and 28d compressive strength of impact-resistant concrete were tested with reference to GB / T50081-2002 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete". The test results are detailed in Table 6.
[0102] Rebound rate: Rebound rate = amount of landed material / total amount of spraying × 100%. The rebounded material is collected by woven cloth and then weighed. The total amount of spraying is calculated by the weight of the material added once. The test results are shown in Table 6.
[0103] Table 6 Performance test results of high-efficiency enhanced shotcrete in different application examples and comparative examples
[0104]
[0105]
[0106] The test results in Table 6 show that the 7d compressive strength and 28d compressive strength of the high-efficiency enhanced shotcrete obtained in the present application are not much different, with the highest being 44.96MPa and 76.77MPa, respectively, indicating that the high-efficiency enhanced shotcrete admixture of the present application will not affect the compressive strength of the concrete; however, the rebound rate of the high-efficiency enhanced shotcrete is reduced from 9.31% to 6.25%, which significantly reduces the rebound rate of the high-efficiency enhanced shotcrete.
[0107] In Application Examples 1-4, the rebound rate of the high-efficiency enhanced shotcrete obtained in Application Example 4 is 8.95%, which is lower than that of Application Examples 1-3, and has a lower rebound rate. This indicates that it is more appropriate to add sulfonic acid modified polyacrylic acid emulsion to the raw materials of the high-efficiency enhanced shotcrete admixture, which reduces the rebound rate of the shotcrete. This may be related to the fact that the sulfonic acid modified polyacrylic acid emulsion provides a bridging effect to bridge the raw material particles in the shotcrete, thereby increasing the slurry yield stress and plastic cohesion, and increasing the cohesion of the concrete.
[0108] In application examples 5-8, the rebound rate of the high-efficiency enhanced shotcrete obtained in application example 5-7 is 8.36-8.62%, which is lower than that in application example 8, and has a lower rebound rate. It shows that when the weight ratio of methylenebisacrylamide and vinyl acetate is controlled to 1: (1.2-2), it is more suitable, which reduces the rebound rate of shotcrete. It may be related to the fact that controlling the weight ratio of methylenebisacrylamide and vinyl acetate can increase the plastic viscosity of sulfonic acid modified polyacrylic acid emulsion and increase the cohesiveness of concrete.
[0109] In application examples 9-13, the rebound rate of the highly efficient reinforced shotcrete obtained in application example 13 is 7.42%, which is lower than that of application examples 9-12, and has a lower rebound rate. This indicates that when the cosolvent in the composite of long-chain silane-modified nanofibers and fluorinated epoxy resin emulsion is a mixture of lauric acid and ethylene glycol butyl ether, it is more suitable and reduces the rebound rate of the shotcrete. This may be related to the fact that the addition of the mixture of lauric acid and ethylene glycol butyl ether can increase the crosslinking density of the composite of long-chain silane-modified nanofibers and fluorinated epoxy resin emulsion.
[0110] In application examples 13-17, the rebound rate of the highly efficient reinforced shotcrete obtained in application examples 14-16 is 6.95-7.21%, which is lower than that of application examples 13 and 17, and has a lower rebound rate. It shows that when the weight ratio of lauric acid and ethylene glycol butyl ether in the raw material of the long-chain silane-modified nanofiber and the fluorine-containing epoxy resin emulsion composite is controlled to be 1: (1-2), it is more appropriate to reduce the rebound rate of the shotcrete. It may be related to controlling the weight ratio of lauric acid and ethylene glycol butyl ether to be 1: (1-2), further improving the compatibility of the long-chain silane-modified nanofiber and the fluorine-containing epoxy resin emulsion composite.
[0111] In application examples 18-21, the rebound rate of the highly efficient enhanced shotcrete obtained in application examples 18-20 is 6.25-6.51%, which is lower than that in application example 21, and has a lower rebound rate. This indicates that when the weight ratio of methylenebisacrylamide and vinyl acetate is controlled to be (0.5-0.8):1 in the preparation of sulfonic acid modified polyacrylic acid emulsion, it is more appropriate to reduce the rebound rate of shotcrete. This may be related to the fact that the cross-linking effect of polyacrylic acid emulsion can be enhanced by controlling the weight ratio of methylenebisacrylamide and vinyl acetate to (0.5-0.8):1.
[0112] In addition, combining the various index data of the high-efficiency enhanced shotcrete of application comparison examples 1-5 and application examples 1-21, it is found that the addition of long-chain silane-modified nanofibers and fluorine-containing epoxy resin emulsion composites to the raw materials of the high-efficiency enhanced shotcrete admixture can improve the compressive strength of the high-efficiency enhanced shotcrete to varying degrees and effectively reduce its rebound rate.
[0113] This specific application example is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the application example without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.
Claims
1. A highly efficient enhanced shotcrete admixture, characterized in that: The invention comprises the following raw materials in parts by weight: 10-30 parts of polycarboxylate water-reducing agent; 15-30 parts of vegetable glue; 80-110 parts of nanofiber and epoxy resin composite; 30-70 parts of accelerating setting agent; 5-10 parts of water; the nanofiber and epoxy resin composite is a composite of long-chain silane-modified nanofiber and fluorine-containing epoxy resin emulsion; The nanofiber and epoxy resin composite is a composite of long-chain silane-modified nanofiber and fluorine-containing epoxy resin emulsion and is prepared by the following steps: Step S1: 2-8 kg of toluene diisocyanate is dissolved in an organic solvent, heated to 50-100° C., stirred, a catalyst is added, reacted for 1-3 hours, 2-8 kg of fluorine-containing organic matter is added, washed and dried to obtain a fluorine-containing modifier; Step S2: after mixing the fluorine-containing modifier prepared in step S1, 10-20 kg of bisphenol A diglycidyl ether, and 3-5 kg of diluent, 0.3-1 kg of curing agent is added, and curing is performed at 80-150° C. for 5-8 hours to obtain a fluorine-containing epoxy resin emulsion; Step S3: under acidic conditions, adding 2-10 kg of long-chain silane to ethanol and aqueous solution, heating and stirring, then adding 50-80 kg of nanofibers and stirring, and after drying, adding the fluorine-containing epoxy resin emulsion obtained in step S2 and 8-16 kg of co-solvent, heating and stirring, and then washing and drying to obtain a composite of long-chain silane-modified nanofibers and fluorine-containing epoxy resin emulsion; The fluorine-containing organic compound is 3-fluorocatechol; the long-chain silane is hexadecyldimethylchlorosilane; and the nanofiber is a nanofiber capable of cross-linking the long-chain silane through Si-O chemical bonds.
2. The high-efficiency reinforced shotcrete admixture according to claim 1, characterized in that: The cosolvent is a mixture of lauric acid and ethylene glycol butyl ether.
3. The high-efficiency reinforced shotcrete admixture according to claim 2, characterized in that: The weight ratio of the lauric acid to ethylene glycol butyl ether is 1:(1-2).
4. The high-efficiency reinforced shotcrete admixture according to claim 1, characterized in that: The vegetable gum is selected from at least one of wenan gum, xanthan gum and konjac gum.
5. The high-efficiency reinforced shotcrete admixture according to claim 1, characterized in that: The raw materials also include 5-20 parts by weight of sulfonic acid modified polyacrylic acid emulsion.
6. The high-efficiency reinforced shotcrete admixture according to claim 5, characterized in that: The sulfonic acid modified polyacrylic acid emulsion is prepared by the following steps: Acrylic acid monomer, sodium allyl sulfonate, methylene bisacrylamide and vinyl acetate are mixed, heated to 30-50°C, then a chain transfer agent and an initiator are added and stirred for reaction, and finally hydrogen peroxide is added and stirred for 10 minutes to obtain a sulfonic acid modified polyacrylic acid emulsion.
7. The high-efficiency reinforced shotcrete admixture according to claim 6, characterized in that: The weight ratio of methylenebisacrylamide to vinyl acetate is 1:(1.2-2).
8. The high-efficiency reinforced shotcrete admixture according to claim 5, characterized in that: The weight ratio of the sulfonic acid modified polyacrylic acid emulsion and the polycarboxylic acid water reducer is (0.5-0.8):
1.
9. Use of the high-efficiency enhanced shotcrete admixture according to any one of claims 1 to 8 in shotcrete, characterized in that: The addition amount of the high-efficiency enhanced shotcrete admixture is 0.5-8% of the cement mass.
Citation Information
Patent Citations
Liquid accelerator for sprayed concrete and preparation method and application thereof
CN103664034A
Nano high-strength shotcrete reinforcing agent and application thereof
CN111320408A